Seven-Core Fiber Composite Structures-Based Mach-Zehnder Interferometer for Bending and Temperature Measurement - Zhang, Kai; Ling, Qiang; Chen, Yao; Luo, Si; Zhang, Yusheng; Zhou, Yan; Feng, Gaofeng; Yang, Junyong; Yu, Zhangwei; Chen, Haiyun; Jiang, Xiuli; Guan, Zuguang; et al. (Photonic Sensors, 2024)
In the paper, an optical fiber sensor based on a seven-core fiber composite structure is presented, which enables dual-parameter sensing of bending and temperature. The proposed structure is fabricated by combining the strongly-coupled seven-core fibers (SC-SCFs) and a weakly-coupled seven-core fiber (WC-SCF). The SC-SCF acts as a beam coupler and enhances the Mach-Zehnder interference, while the WC-SCF serves as the enhanced section of another Mach-Zehnder interference. Therefore, the spectrum response of the fiber structure mentioned above exhibits a superposition effect of two Mach-Zehnder interferometers (MZIs). Among them, two dips corresponding to different MZIs are used to measure bending and temperature. The experimental results show the bending sensitivity and temperature sensitivity of the two MZIs are −4.238 nm/m−1, −2.263 nm/m−1, 0.047 nm/°C, and 0.064 nm/°C, respectively. It proves that our sensor is very sensitive to bending. Through the dual-wavelength matrix method, the bending and temperature can be measured simultaneously. With the benefit of the composite structure, low cost, and ease of fabrication, the proposed sensor can be used in harsh environments.